Early Purchasing Involvement in New Product Development - Opportunities for Environmental Sustainability - Hyyryläinen, Satu (2012)
Purpose – The purpose of this dissertation is to identify what early purchasing involvement in product development consists of, in particular at operational level. A broad analysis of existing literature on new product development, materials selections, purchasing involvement in new product development, sourcing strategy and environmental sustainability is conducted. The objectives of this research are to investigate what factors influence the most in materials selection and how is environmental sustainability currently considered in today’s organisations. The aim is to find out whether early purchasing involvement can support the selection of greener raw materials into product design and improve delivery capability of the product during and after launch and, if so, how.